Peningkatan Literasi Numerik Siswa Melalui Penggunaan Alat Peraga Matematika di SDN Proman - Nugroho, Ronan A.; Zhurifa, Alya; Hidayat, Adrian; Jannah, Faridatul; Mutiara, Kania D.; Arfani, Ahmad N.; Pradhata, Yoga A.; Oktaviani, Windi; Widiastuti, Renita; Nugroho, Bambang W. (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This empowerment initiative aims to emphasize the importance of using teaching aids in mathematics education to enhance students' numerical literacy in elementary schools. Numerical literacy is a fundamental aspect of primary education, yet Indonesian students remain below the international average in this skill. Monotonous teaching strategies and the lack of teaching aids contribute to the low numerical literacy levels among students. This community service program seeks to improve the quality of education in remote areas by supporting the enhancement of students' numerical literacy through the use of mathematical teaching aids. The methods employed include planning through Focus Group Discussions (FGDs), followed by Classroom Action Research, which is implemented in three stages: socialization, training, mentoring, and evaluation. The planning stage involves collaboration among three key stakeholders: the Community Service Team, the school, and students' parents/guardians. The socialization and training phase includes hands-on activities where students create their own teaching aids, culminating in a mathematics teaching aid festival. The evaluation process is conducted through observations, interviews, discussions, and surveys. Evaluation results based on teachers' responses indicate improvements in students' understanding of mathematical concepts, enthusiasm, and creativity. Therefore, this program has effectively enhanced students' numerical literacy through the use of mathematical teaching aids. Sustained collaboration between schools, university students, and the education community is essential to ensure the program's continuity